Learner-Centered English Teaching in a Blended Learning Setting during COVID-19 Pandemic - RAMOS, ARIEL; Jugarap, Krizia Mae; Manalili, Kristin Joy; Calle, Mary Christine; Caruzca, Jane Marie (Future Science / FSH-PH Publications, 2023)
The COVID-19 crisis brought worldwide changes in education resulting to employment of blended learning in schools. In this context, teachers hold classes in both online and traditional learning mode. This new landscape demands knowledge in terms of effectiveness of the widely advocated learner-centered method. Hence, with the participation of university students, the researchers conducted this quasi-experimental study. In addition, the study used inferential statistical treatments to determine the difference of participants’ performance. Results show that there is significant difference in the performance of the participants before and after exposure to learner-centered method in blended learning modality. Therefore, the researchers recommend the adoption of learner-centered method even in the new landscape of the academe now embracing the blended learning.